2021
DOI: 10.1088/1755-1315/632/4/042033
|View full text |Cite
|
Sign up to set email alerts
|

Deformation analysis of underground powerhouse of a large hydropower station based on FLAC3D

Abstract: Aiming at the deformation characteristics of surrounding rocks in underground powerhouse area of a hydropower station in Western China, the finite difference method is used for numerical calculation, and a assistant modeling software is used to realize the refined modeling of complex surface, which effectively improves the simulation accuracy. The results show that the stress level of surrounding rocks is low, the deformation of surrounding rocks is small, and the surrounding rocks is basically stable. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…ey are substituted into equation (12) to obtain the equivalent internal friction angle under different slope coefficients, and then, they are substituted into equation (22) to further obtain the equivalent cohesion. Table 2 lists the equivalent strength parameters of different strata dip angles under different slope coefficients, and the shear modulus in the simulation process is taken (Table 3).…”
Section: Parameter Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…ey are substituted into equation (12) to obtain the equivalent internal friction angle under different slope coefficients, and then, they are substituted into equation (22) to further obtain the equivalent cohesion. Table 2 lists the equivalent strength parameters of different strata dip angles under different slope coefficients, and the shear modulus in the simulation process is taken (Table 3).…”
Section: Parameter Calculationmentioning
confidence: 99%
“…ey found that the horizontal internal extrusion of the surrounding rock was greater than the settlement of the vault, and the lateral wall was largely damaged by horizontal bending and layer separation. Ma [22] modeled the complex curved surface of the underground powerhouse of a hydropower station in western China and simulated it using finite difference software. ey concluded that the deformation and stress of the surrounding rock of the underground powerhouse are small, and the plastic zone has a penetrating trend.…”
Section: Introductionmentioning
confidence: 99%
“…They determined the maximum stress in different directions and pinpointed the location of maximum stress within the hydropower station structure. Ma et al [17] examined the deformation characteristics of the surrounding rock within a subterranean powerhouse and found that the surrounding rock remains stable with low stress and deformation. Elastic cushions have been widely used in water conservancy projects to prevent the spiral case's IWP from being transmitted to the outer concrete and fully leverage the bearing capacity of the metal spiral case.…”
Section: Introductionmentioning
confidence: 99%